Diffuse leprosy with "deck-chair" sign - M Manjunath Shenoy; Mukhtar Ahmed Bendigeri; Prshanth R Kamath; B Vishal (Wolters Kluwer Medknow Publications, 2015)
A 55-year-old male presented with asymptomatic extensive skin lesions since one year. He was found to have diffuse lesions involving the face, trunk, arms, and thighs along with symmetric peripheral nerve thickening. Bacteriological and histopathological examination confirmed lepromatous leprosy. There was a conspicuous sparing of the abdominal creases and axillae from the infiltrative lesions suggesting a positive "deck-chair" sign. This sign has been described in the past with papulo-erythroderma of Ofuji and certain other disorders. Leprosy may be now included among the causes of "deck-chair" sign.